Analisis Pengaruh Fraud Hexagon Dalam Mendeteksi Potensi Kecurangan Laporan Keuangan - Ayu Tri Rahmawati; Endang Sri Utami (Jurnal Riset Akuntansi dan Bisnis, 2023)
The study aims to detect potential fraud in financial statement by using hexagon fraud theory which consists of pressure, opportunity, rationalization, capability, arrogance, and collusion. These elements are proxied using variables financial stability, external pressure, financial targets, nature of industry, change in auditors, change in directors, CEO’s picture, and government project and financial statements fraud as measured using the F-Score Model. Method purposive sampling used in this study, and a sample of 63 companies was obtained from a total of 92 mining sector companies listed on the Indonesia Stock Exchange during the 2016-2019 observation period. The analysis techniques were used is multiple linear regression with the SPPS program 25 version. The result of this study explain that the variables financial target has a positive effect and the change in director variable has a negative effect on fraudulent financial statements. Meanwhile the variables financial stability, external pressure, change in auditors, CEO’s picture and cooperation project with government have no significant effect on fraudulent financial statements.